PHYSIOTHERAPY MANAGEMENT FOR DROP FOOT: A CASE REPORT - Pratama, Cafin Surya Putra; Sari, Dwi Rosella Komala; Widiatmi, Sri (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Drop Foot is a gait disorder that drops the foot forward due to weakness, irritation or damage to peroneal nerve, and paralysis of the muscles in the back of the foot. This is usually a symptom of a bigger problem, not the disease itself. It is characterized by inability or impairment to raise the toes or lift the foot from ankle. Based on data quoted from the Agency for Healthcare Research and Quality (AHRQ), throughout 2009 in the United States there were 1.787 patients who experienced drop foot in hospitals. In the UK, there are 126.699 patients will experience unilateral and bilateral foot drop. Case Presentation: A 26-year-old man was involved in a traffic accident on 1 years ago when he worked in a mine located at East Kalimantan, Samarinda. One day he was going to work form home had a traffic accident with fracture arm and with a deep open wound at medial leg. He was unconscious for 3 days after the accident. After 4 months of being treated in Samarinda, the patient moved to Surabaya because he followed his wife worked. He was treated at UNAIR Hospital for 4 months. Thus, he moved to Klaten and stayed at his family’s place and started doing treatment at Klaten Islamic Hospital. Management and Outcome: Functional Electrical Stimulation (FES), Ankle and Foot Orthoses (AFO), Exercise can increase muscle strength and functional activity that measured by Manual Muscle Test (MMT) and Foot and Ankle Disability Index (FADI) Discussion: FES was able increase muscle strength. Its mechanism is based the depolarization of axons by an electric field. A bidirectional action potensial, activating the motor unit direct depolarization of muscle can used to stimulate the general peroneal nerve, activating the dorsiflexor muscles of the foot during the swing phase of the gait. The AFO improved subtalar joint motion, while also providing stability anterior-posterior and medial-lateral. AFO has beneficial effects in term of improving functional mobility, gait quality and decreased fall rates in these subjects. Therapeutic exercise was a systematic and planned performance intended body movement, posture, or physical activity to provide patients/clients with the means to fix or prevent impairment, repairing, restoring or improving physical function, prevent or reduce health-related risk factors, optimize your health status, fitness, or overall sense of wellbeing. Conclusion: The treatment of Functional Electrical Stimulation (FES), Exercise, and Ankle Foot Orthoses (AFO) in this case is to be useful for patients with foot drop cases caused by nerve damage after a traffic accident, increase muscle strength and increase functional activity.